TRADITIONAL HORN PROCESSING, COMB AND JEWELRY DESIGNS IN SİVAS - SAKLAVCI , Fatmagül (SSD Journal, 2021)
Horn embroidery is one of the traditional handicrafts of Sivas that is about to disappear. It shows that bone combs and items found in excavations in Sivas and its surroundings were used by many cultures that lived before. Due to the harmony of the keratin inside with the human skin, the horn, which was used mostly in the making of combs in the historical process, musical instrument accessories, knife handle, rosary, jewelry, are processed. In the past, cattle, bull and carob were also used, but today ram and buffalo horns are processed. The raw horn is dried and the buttonhole part called the core is dropped, and the dried pieces are cut in sizes to be used. These parts are turned into raw materials by being heated and pressed in the fired fire so that they do not bend in the future. In comb making, the horn is sequentially treated, rasping, teeth opening, grating, and finally it is polished and put into use. Since the produced parts are made by hand and the inside of each horn is different from each other like fingerprints, their sizes, colors and patterns differ from each other. Since there are no masters working in antlers in Sivas recently, combs and accessories that are identical in size and size are brought from abroad due to their production features. Fatih Duran, whose main profession was knife making, started to apply the methods and techniques of traditional horn processing in his own workshop with following his personal efforts and the works of previous masters, and he tries to keep this art alive by educating himself. In Duran's workshop, while making knife handle and comb, another artist, Hayati Ünsal, takes horn embroidery to another dimension by making handcrafted ornaments to comb and jewelery made by Duran. In our study, the environments where these people work were visited and the materials, techniques and works they produced were introduced and information was given. This workmanship, which requires a lot of effort and effort, is waiting for people who will devote their hearts and will learn and pass it on to future generations.